An experimental study of the intrinsic fluorescence emission and Electrochemically Induced Ageing in poly-o-methylaniline films - Marmisollé, Waldemar Alejandro (2013)
The intrinsic fluorescence emission of poly(o-methyl aniline) (Pma) films electrodeposited upon gold electrodes was studied. As this electrochemically active polymer becomes oxidized, the fluorescence diminishes as a consequence of the charge carriers injected into the film that act as quenchers of the excited states. Additionally, it is shown that the fluorescence emission can be employed to monitor the Electrochemically Induced Ageing, a characteristic phenomenon of this type of conducting polymers. The ageing rates of Pma films, in terms of the fluorescence intensity are compared with those determined from the voltammetric response for films of different thicknesses (ca. 0.3–3 μm). Similarities with physical ageing experiments are discussed.